Exploring The Viability Of Holistic Human Resources Development In Addressing Unethical Conduct In Federal Ministries Of Malaysia - Saleem, Muhammad (2024)
This study aims to highlight the significance of spiritual quotient (SQ) programs in the process model of human resource development (HRD). This study had conducted an in-depth interview to the respondent from few Federal Ministries of Malaysia.